DISTRIBUTION OF MANAGEMENT OF AUTHORITY IN MANAGEMENT OF MARINE NATURAL RESOURCES BASED ON REGIONAL ADMINISTRATION LAW - Djou, Azis Kasim; Shahrullah, Rina Shahriyani; Syarief, Elza (Universitas Internasional Batam, 2023)
The enactment of Law Number 30 of 2014 concerning Government Administration, it certainly provides clear directions regarding the implementation of governance, encompassing the acquisition and exercise of authority, as well as prohibitions against the misuse of authority. The distribution of authority, finances, utilization of natural resources, and other resources are conducted fairly and harmoniously between the central government and regional governments. Similarly, the arrangement of authority distribution in the management of marine natural resources stipulates that the management of marine natural resources from the coastline up to a distance of 12 nautical miles beyond oil and natural gas falls under the jurisdiction of provincial regional governments. However, up to this point, the collection of fees for utilization remains under the control of the central government through technical implementation units in the region. This research employs a juridical-empirical method with a legislative approach, analyzing its effectiveness based on its implementation within the province of Riau Islands. The study is conducted using a qualitative method and described in a descriptive manner. The research findings indicate that the regional government does not benefit from the management of marine natural resources in the port sector, particularly concerning the collection aspects of the utilization of marine natural resources within the 0 to 12 nautical miles in the regional government's territory.